Dual VET in the EU policy: the internationalization of the german model? - Martínez-Izquierdo, Luis; Pereyra-García Castro, Miguel; Torres-Sánchez, María Mónica (My University, 2022)
Some European countries, including Spain, encouraged by the European Union, have undertaken the reform of their Vocational Training systems so as to promote dual apprenticeship. This research analyses EU documentation, consisting of documents related to the Copenhagen process and VET reform, such as communications, recommendations, and declarations from different European bodies. This analysis will focus on EU proposals and recommendations on two areas of VET: the governance system and the training model which are the main characteristics of the German model of VET. The methodology consists of reflective thematic analysis, using NVIVO's qualitative data analysis computer software. This will advance the understanding of the process of internationalisation and attraction of the German dual VET model within the EU as a model of good practice.
Keywords: Enseñanza - Investigación; Educación comparada; Enseñanza profesional; Países de la Unión Europea - Política educativa; Vocation Education Training (VET); Policy analysis; Europeanisation